UTILIZATION SIX BOX MODELS TO SOLVE THE PROBLEM IN NON- PROFIT ORGANIZATION CASE STUDY IN KELUARGA MAHASISWA CIAMIS GALUH TARUNA - Aldriyan, Alfi; Febriansyah, Hary (Journal of Business and Management, 2017)
AbstractÂ Based on the meeting of Galuh Taruna members on August 10, 2016 has been discussed in the organization Galuh Taruna there are 3 issues including leadership, organizational relationships, and organizational structure. Researchers want to do research on Organizational Development to get a solution to the phenomenon. This research uses qualitative approach with ethnography method. Then the researchers used the Six Box as an instrument to perform the analysis. Methods of data collection conducted using semi-structured interview method. While for data validation, researcher use triangulation data based on source. The researcher found that there are problems in leadership style, commitment of chairman, bad habits of chairman, organizational culture, organizational structure, organizational goals that lead to politics, and absence of reward system. After the researchers apply the six boxes to solve the problem, then found a solution such as the chairman must be often involved in the activities of the organization, the chairman must have a high commitment to the organization, the chairman must be an example for its members, dual positions system is not allowed, avoiding activities that smelled of politics, Riung Galuh activities, as well as applying the appreciation of certificate.